2022
DOI: 10.36897/jme/146533
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Compliance Measurement of a Clamping Table with Integrated Force Sensors

Abstract: Force sensor integration into machine components is a promising approach to measure spatial process forces, especially, when regarding hexapod structures and kinematics. Rigid still-standing hexapod frameworks, such as clamping tables, are particular suitable for this approach, as no dynamic influences need to be taken into account within the measurement model and they allow a measurement in 6 degrees of freedom. On the other hand, the stiffness of rigid frameworks is reduced by force sensor integration signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
(13 reference statements)
0
0
0
Order By: Relevance
“…For these characteristics, similar systems are widely used in flight simulators. Additional applications and studies can be found, for example, in (Qazani, Pedrammehr, and Nategh 2018;Butzhammer, Müller, and Hausotte 2023;Pedrammehr et al 2014;Friedrich and Ihlenfeldt 2022).…”
Section: Machine Descriptionmentioning
confidence: 99%
“…For these characteristics, similar systems are widely used in flight simulators. Additional applications and studies can be found, for example, in (Qazani, Pedrammehr, and Nategh 2018;Butzhammer, Müller, and Hausotte 2023;Pedrammehr et al 2014;Friedrich and Ihlenfeldt 2022).…”
Section: Machine Descriptionmentioning
confidence: 99%